STRATEGI KEPALA SEKOLAH DALAM MENGIMPLEMENTASIKAN PROFIL PELAJAR PANCASILA DI SEKOLAH DASAR ISLAM TERPADU - Khairani; Wiwik Okta Susilawati; Dian Estu Prasetyo (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This study was conducted because of the excellence in SD IT Andalas Cendekia, especially in religious values and other general achievements. This study aims to determine the strategies used by the principal in implementing the Pancasila student profile of the dimensions of faith, devotion to God Almighty and noble character in SD IT. The type of research used is qualitative research. The results of the study found four types of principal strategies and success in implementing them in SD IT: 1) learning activities (students can remind each other of good things). 2) development of school culture / daily school activities, it was found that students had followed school regulations such as, dhuha prayer, easy to admit mistakes and apologize, for those at the high class level they were disciplined in maintaining their genitals, limits on socializing, and forming a personality that was devoted to God Almighty. 3) extracurricular (self-development), it was seen that students achieved achievements from various competitions, were able to develop talents according to their interests and had higher self-confidence. 4) daily activities at home and in the community, there are students who are able to directly practice good manners in real life, are able to recognize prayer times and carry them out on time, and are more open in interacting.